Effect of Storage Time at Low Temperature on Physico-Chemical Characteristics of Eggs from Hens Kept in Backyard System in the City of Iasi in Romania - Francois Djitie Kouatcho; Marius Georgi Usturoi; Razvan Mihail Radu-Rusu; Aida Albu; Eliza Simiz (Scientific Papers Animal Science and Biotechnologies, 2023)
Egg production is an excellent solution to the acute shortage of animal protein. Despite its ability to be stored for several days at room temperature, eggs are an extremely perishable foodstuff whose optimal conservation standards must be mastered. The present study was carried out with the aim of evaluating the effect of storage time at low temperature on the physico-chemical characteristics of eggs from hens kept in backyard systems in the city of Iasi in Romania. For this purpose, 180 hen eggs were purchased on the local market. Once in the laboratory, the eggs were cleaned, marked and then stored in the refrigerator at a temperature of approximately 5ºC. The next day and every 7 days after, external characteristics (weight, measurements, shape indexes, volume and density) of all the eggs were evaluated and 60 eggs were then used for the analysis of internal characteristics (yolk and albumen indexes, Haugh unit, proportion of white, yolk, shell, edible parts) and chemical characteristics (pH, dry matter content, ash, proteins and lipids) of the eggs. The main results show that, except for density, which decreased with storage time, other external characteristics of eggs remained similar. The same was true for the major internal parameter characteristics. The pH of the yolk and albumen increased with the storage time, which also led to a variation in the contents of dry matter, ash, lipids and proteins of the egg components. It was concluded that although refrigeration allows the external characteristics of eggs from the backyard system to be kept relatively constant, storage time does, however, affect the chemical characteristics of the eggs. Refrigeration of eggs slows down but does not prevent the deterioration of the eggs and consequently they cannot be stored indefinitely.